Respuesta :
Simplifying
4n + -19 = 13
Reorder the terms: -19 + 4n = 13
Solving -19 + 4n = 13
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '19' to each side of the equation. -19 + 19 + 4n = 13 + 19
Combine like terms: -19 + 19 = 0 0 + 4n = 13 + 19 4n = 13 + 19
Combine like terms: 13 + 19 = 32 4n = 32
Divide each side by '4'. n = 8
Simplifying n = 8
Reorder the terms: -19 + 4n = 13
Solving -19 + 4n = 13
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '19' to each side of the equation. -19 + 19 + 4n = 13 + 19
Combine like terms: -19 + 19 = 0 0 + 4n = 13 + 19 4n = 13 + 19
Combine like terms: 13 + 19 = 32 4n = 32
Divide each side by '4'. n = 8
Simplifying n = 8
--Move 19 to the right side and change its sign- 4(n)=13+19
--Add the numbers - 4(n)=32
--Divide both sides by 4
--n=8
--Add the numbers - 4(n)=32
--Divide both sides by 4
--n=8